2019
DOI: 10.3892/mmr.2019.10143
|View full text |Cite
|
Sign up to set email alerts
|

Signature microRNAs and long noncoding RNAs in laryngeal cancer recurrence identified using a competing endogenous RNA network

Abstract: The aim of the present study was to identify novel microrna (mirna) or long noncoding rna (lncrna) signatures of laryngeal cancer recurrence and to investigate the regulatory mechanisms associated with this malignancy. datasets of recurrent and nonrecurrent laryngeal cancer samples were downloaded from The cancer Genome atlas (TcGa) and the Gene expression omnibus database (GSe27020 and GSe25727) to examine differentially expressed mirnas (de-mirs), lncrnas (de-lncrs) and mrnas (deGs). mirna-mrna and lncrna-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 62 publications
0
20
2
Order By: Relevance
“…Tang et al identified that low expressions of Emx2os are closely associated with longer DSF and OS ratio in LSCC patients based on in silico analysis of databases. They also indicated that Emx2os regulates the expression of CALCA and GABRG2 through miR-124 [ 70 ]. We have also observed that high expressions of snaR and SNHG1 was correlated with a favorable OS in HNSCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al identified that low expressions of Emx2os are closely associated with longer DSF and OS ratio in LSCC patients based on in silico analysis of databases. They also indicated that Emx2os regulates the expression of CALCA and GABRG2 through miR-124 [ 70 ]. We have also observed that high expressions of snaR and SNHG1 was correlated with a favorable OS in HNSCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…LINC00488 functions as a ceRNA to regulate hepatocellular carcinoma cell proliferation and angiogenesis through miR-330-5 (17). Coding RNAs interact with non-coding RNAs through microRNA (miRNA/miR) response elements, thus influencing cellular communication, transcription regulation and biological functions (16)(17)(18). The bioinformatics analysis identified that miRNA-485-5p is the downstream gene of LINC00488.…”
Section: Introductionmentioning
confidence: 99%
“…including AC005104.1, AC093278.2, AC098484.1, AL360181.2, LINC01011, AP001372.2, AC007637.1, AL354733.3, and AP001189.3, which were the first time that served as markers in the current research. The lncRNA EMX2OS, which has been validated and identified to potentially induce proliferation and invasion, and promote sphere formation in ovarian cancer cells by regulating the miR-654-3p/AKT3/PD-L1 Axis 28 Additionally, EMX2OS can be used as a biomarker in laryngeal cancer and papillary thyroid cancer 29 , 30 . Furthermore, SPINT1-AS1 was identified as a potential marker in the prognosis of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%